STRATEGIC MANAGEMENT ANALYSIS OF NATIONAL CONVENIENCE STORE CHAIN A: RECOVERY STRATEGY FOR OPERATIONAL EFFICIENCY AND PRODUCTIVITY - Kirana Ainayya Mumtazah; Muhammad Rifandito Rahmantio; Ryco Syaputra; Tiara Puspa (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2025)
National convenience store chain A faces intense retail competition, market saturation, and digital disruption that require a structured strategic response. This study aims to formulate a strategic priority for improving the operational efficiency, outlet productivity, and competitiveness of national convenience store chain A by applying the strategic management framework of David and David. Using a descriptive strategic analysis approach, this study employs the IFE, EFE, CPM, SWOT, and QSPM matrices.The input stage shows that national convenience store chain A has a strong internal position (IFE = 2.97) and an above-average response to external opportunities and threats (EFE = 2.99). The Competitive Profile Matrix indicates that national convenience store chain A remains highly competitive (3.82), although it is slightly below national convenience store chain B (3.92) and above national convenience store chain C (2.92) and international convenience store chain D (2.28).The SWOT matrix produces three feasible alternatives, while the QSPM identifies AS1 (accelerating omnichannel, loyalty, and digital store services) as the most attractive option with a TAS of 6.30, followed by AS3 (6.19) and AS2 (6.08). Therefore, national convenience store chain A should prioritize digital service acceleration and use its extensive physical network to strengthen customer experience, quick transactions, and sustainable retail productivity.